Uma leitura midiática sobre o fortalecimento institucional do Ministério Público na Constituinte de 1987/88 - Ribeiro, Desirée Ferreira Marques (Universidade Federal de São Carlos, 2021)
The gradual obtaining of prerogatives from the Federal Prosecution Service started in the dictatorial period and enshrined with the promulgation of the 1988 Constitution, points to a course of institutional strengthening. This development was accompanied by the national press, with articles portraying the protagonists of the debates in this context. This monograph aims to reconstruct this process from the news coverage, identifying actors in dispute, regarding the MPF's prerogatives, during the 1987/88 National Constituent Assembly. The theoretical approach starts from the Bourdieusian concept of the field to identify the narratives and forces in dispute. The methodology is based on document analysis based on three strategies: 1) analysis of news content published by the newspapers “O Estado de S. Paulo” and “Folha de S. Paulo”, between 1985 and 1988; 2) exploratory bibliography study that addresses the lobby carried out by the Federal Prosecution Service; and 3) documentary analysis of the preliminary draft approved by the Subcommittee of the Judiciary and the Federal Prosecution Service, as well as the articles referring to the MPF in the constitutional text promulgated in 1988. The media outlined a positive portrait in defense of an institution's prerogatives and attributions that it was beginning to emerge as a defender of society and that, therefore, constituted a substantial legal protection against the arbitrariness experienced in the regime of exception. There was a congruence between the content of the speeches conveyed by the news coverage, by the MPF, by the preliminary draft of the SPJMP and, in large part, by the constitutional text approved in 1988.
A media reading on the institutional strengthening of the Federal Prosecution Service in the 1987/88 Constituent Assembly
Keywords: Ministério Público Federal; Constituinte; Transição democrática; Campo jurídico; CIENCIAS HUMANAS::SOCIOLOGIA